Intrahepatic cholangiocarcinoma prognostic determination using pre-operative serum C-reactive protein levels. Issue 1 (December 2016) - Lin, Zi-Ying; Liang, Zhen-Xing; Zhuang, Pei-Lin; Chen, Jie-Wei; Cao, Yun; Yan, Li-Xu; Yun, Jing-Ping; Xie, Dan; Cai, Mu-Yan
Abstract Background Serum C-reactive protein (CRP), an acute inflammatory response biomarker, has been recognized as an indicator of malignant disease progression. However, the prognostic significance of CRP levels collected before tumor removal in intrahepatic cholangiocarcinoma requires further investigation. Methods We sampled the CRP levels in 140 patients with intrahepatic cholangiocarcinoma who underwent hepatectomies with regional lymphadenectomies between 2006 and 2013. A retrospective analysis of the clinicopathological data was performed. We focused on the impact of serum CRP on the patients' cancer-specific survival and recurrence-free survival rates. Results High levels of preoperative serum CRP were significantly associated with well-established clinicopathologic features, including gender, advanced tumor stage, and elevated carcinoembryonic antigen and carbohydrate antigen 19-9 levels (P < 0.05). Univariate analysis demonstrated a significant association between high levels of serum CRP and adverse cancer-specific survival (P = 0.001) and recurrence-free survival (P < 0.001). In patients with stage I/II intrahepatic cholangiocarcinoma, the serum CRP level was a prognostic indicator for cancer-specific survival. In patients with stage I/II or stage III/IV, the serum CRP level was a prognostic indicator for recurrence-free survival (P < 0.05). Additionally, multivariate analysis identified serum CRP level in intrahepatic cholangiocarcinoma as an independent prognostic factor (P < 0.05). Conclusions We confirmed a significant association of elevated pre-operative CRP levels with poor clinical outcomes for the tested patients with intrahepatic cholangiocarcinoma. Our results indicate that the serum CRP level may represent a useful factor for patient stratification in intrahepatic cholangiocarcinoma management.